A novel strategy for 1, 3-propanediol recovery from fermentation broth and control of product colority using scraped thin-film evaporation for desalination. Issue 60 (2nd July 2015) - Zhang, Yuanman; Luo, Ji'an; Zhao, Xuebing; Liu, Dehua
<x xml:space="preserve">Abstract</x> A novel strategy for 1, 3-propanediol recovery from fermentation broth was developed to control the product colority by adjusting the pH of feeding stream before desalination using a scraped thin-film evaporation.